A drag coefficient for application to the WLTP driving cycle. (August 2017) - Howell, Jeff; Forbes, David; Passmore, Martin
The aerodynamic drag characteristics of a passenger car have, typically, been defined by a single parameter: the drag coefficient at a yaw angle of 0°. Although this has been acceptable in the past, it does not provide an accurate measure of the effect of aerodynamic drag on fuel consumption because the important influence of the wind has been excluded. The result of using drag coefficients at a yaw angle of 0° produces an underprediction of the aerodynamic component of fuel consumption that does not reflect the on-road conditions. An alternative measure of the aerodynamic drag should take into account the effect of non-zero yaw angles, and a variant of wind-averaged drag is suggested as the best option. A wind-averaged drag coefficient is usually derived for a particular vehicle speed using a representative wind speed distribution. In the particular case where the road speed distribution is specified, such as for a driving cycle to determine fuel economy, a relevant drag coefficient can be derived by using a weighted road speed. An effective drag coefficient is determined with this approach for a range of cars using the proposed test cycle for the Worldwide Harmonised Light Vehicle Test Procedure, WLTP. The wind input acting on the car has been updated for this paper using recent meteorological data and an understanding of the effect of a shear flow on the drag loading obtained from a computational fluid dynamics study. In order to determine the different mean wind velocities acting on the car, a terrain-related wind profile has also been applied to the various phases of the driving cycle. An overall drag coefficient is derived from the work done over the full cycle. This cycle-averaged drag coefficient is shown to be significantly higher than the nominal drag coefficient at a yaw angle of 0°.